(untitled) (Ameghiniana, 2013)
The present paper deals with the descriptions of new petrified specimens of Pentoxylon sabnii and Nipaniophylium raoi collected from the fossiliferous locality Amarjola in the Rajmahal Hills. Studies of these specimens have enhanced the frontiers of our knowledge about the anatomical details of these plants and thus a better comparison can now be made with other allied groups oí plants. The author finds a close similarity in the anatomical structures of Pentoxylon "nd the Triassic stem genus Rhexoxylon. He also confirms the cycadean nature of the epidermis of the frond Nipaniopbyllum raoi.